Bioerosion caused by the sea urchin Diadema mexicanum (Echinodermata: Echinoidea) at Bahías de Huatulco, Western Mexico - Herrera-Escalante, T. (2005)
Mexican Pacific sea urchin studies have been focused mainly on species distribution, ecology and fisheries. Reef degradation by sea urchin bioerosion has not been studied previously en these reefs. We investigate the importance of Diadema mexicanum as a bioerosive agent of coral carbonate at Bahías de Huatulco, and the relative magnitude of coral accretion and bioerosion. At each of five localities in Bahías de Huatulco, sea urchin density, feeding and mechanical (spine) erosion was determined for three size class intervals. In general, D. mexicanum do not exert any significant role on coral reef community structure (live coral, dead coral or algal coverage) at the Huatulco area, probably because they are generally small (2.9-4 cm test size) and few in number (1.0-6.8 ind.m-2). Mean bioerosion rates are consistent with those measured for other diadematoids, as well as other urchin species in various eastern Pacific localities. However, the degree of bioerosive impact depends on species, test size, and population density of urchins. Coral carbonate removal by D. mexicanum erosion varies from 0.17 to 3.28 kgCaCO3m-2yr-1. This represents a carbonate loss of < 5% of the annual coral carbonate production at Jicaral Chachacual, San Agustín and Isla Cacaluta, but 16 and 27% at Isla Montosa and La Entrega. On balance, coral accretion exceeds sea urchin erosion at all sites examined at Huatulco. At Bahías de Huatulco coral reef communities are actively growing, though in the coming years, it might be necessary to investigate the local effects of the interaction among erosion, and environmental and human induced perturbations. Rev. Biol. Trop. 53(Suppl. 3): 263-273. Epub 2006 Jan 30.